NEPHROPROTECTIVE OF ETHANOL EXTRACT OF Annona muricata L. BARK ON PARACETAMOL-INDUCED NEPHROTOXICITY IN RATS - Widya Sari; Masykur Masykur; Farah Adhilla; Rojatul Maisarah; Fauziah Fauziah (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2023)
Kidneys are organs that have the potential for damage caused by toxic substances. The use of paracetamol in high doses or long-term therapeutic doses can cause adverse effects in the form of damage to the kidneys. Plants that have the potential to become medicinal raw materials against kidney damage are Annona muricata L. The purpose of this study was to determine the potential protection of ethanolic extract of soursop bark (EESB) against histopathological rat kidney induced by toxic doses of paracetamol. This study used an experimental method using a completely randomized design (CRD). The normal control group (K0) and negative control (K-) were given distilled water, while in the treatment group the doses of EESB were 150, 300 and 600 mg/kgBW dissolved in 1 ml of distilled water for 14 days. On the 7th day, all groups of rats were given paracetamol at a dose of 1350 mg/kgBW except for the K0 group. Each group was 5 repetitions, so that in this study used 25 rats (Rattus norvegicus L.). Samples of kidney organs were taken on the 14th day to observe the histopathological structure of the tubular cells undergoing necrosis. The results showed that at a dose of 300 mg/kgBW EESB had the potential for protection against kidney histopathology by suppressing the occurrence of cell death (necrosis).Keywords: Soursop bark, kidney, paracetamol, necrosis